Curcumin Modulates Nitrosative Stress, Inflammation, and DNA Damage and Protects against Ochratoxin A-Induced Hepatotoxicity and Nephrotoxicity in Rats - Consiglia Longobardi; Sara Damiano; Emanuela Andretta; Francesco Prisco; Valeria Russo; Francesco Pagnini; Salvatore Florio; Roberto Ciarcia (MDPI AG, 2021)
Ochratoxin A (OTA) is a fungal toxin of critical concern for food safety both for human health and several animal species, also representing a cancer threat to humans. Curcumin (CURC) is a natural polyphenol that has anti-apoptotic, anti-inflammatory, and antioxidant effects. The aim of this study was to investigate the cytoprotective effect of CURC against OTA-induced nephrotoxicity and hepatotoxicity through the study of the nitrosative stress, pro-inflammatory cytokines, and deoxyribonucleic acid (DNA) damage. Sprague Dawley rats were daily treated with CURC (100 mg/kg b.w.), OTA (0.5 mg/kg b.w), or CURC with OTA by oral gavage for 14 days. Our results demonstrated that OTA exposure was associated with significant increase of pro-inflammatory and DNA oxidative-damage biomarkers. Moreover, OTA induced the inducible nitric oxide synthase, (iNOS) resulting in increased nitric oxide (NO) levels both in kidney and liver. The co-treatment OTA + CURC counteracted the harmful effects of chronic OTA treatment by regulating inflammation, reducing NO levels and oxidative DNA damage in kidney and liver tissues. Histology revealed that OTA + CURC treatment determinates mainly an Iba1+ macrophagic infiltration with fewer CD3+ T-lymphocytes in the tissues. In conclusion, we evidenced that CURC exerted cytoprotective and antioxidant activities against OTA-induced toxicity in rats.